(3QMdI GdEeGe GdTGaYis
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd (B: (3MOKfG GdQHjY Hf SdjeG f,bGd (B: (3SeYJ GdTGaYi QMeg Gddg Ydjg , jbhd (B: (3aGQbJ ecI hCfG GHf CQHY YTQI SfI s
(3BNQgG (B:s
(3agPG LejY eGdbjJg ai SaQi aGage Pdc jG QHjY Je cJGH GdSaQ hddg GdMeO hGdefI hGdUdGI Ydi eMeO GdfHi GdCei hYdi Bdg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eTQa YHO GdcQje GdNGUI HJYR s
Keywords: (3GdJGQjNs